2013
DOI: 10.1039/c3ta12297b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a side chain sequence on surface segregation of regioregular poly(3-alkylthiophene) and interfacial modification of bilayer organic photovoltaic devices

Abstract: A regioregular poly(3-alkylthiophene) with a statistical sequence of alkyl/semifluoroalkyl side chains (stat-P3DDFT) was synthesized through the copolymerization of mixed monomers. The surface segregation behavior was compared with the corresponding alternating copolymer (alt-P3DDFT) that forms highly ordered dipole layers by surface segregation. X-ray and ultraviolet photoelectron spectroscopies of the polymer films revealed that alt-P3DDFT formed a much more ordered surface segregated monolayer than did stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…SSMs were originally developed to form self‐organized buffer layers at the electrode interfaces in OPVs . Later, it was shown that proper design of SSM molecules can control the molecular orientation, structural order, and functionalities at the surface of the films . Furthermore, the electronic structures of the PHJ at the interface can be tuned through the molecular dipoles or the energy structures of the monolayers .…”
Section: Preparation and Characterization Of Planar Heterojunctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…SSMs were originally developed to form self‐organized buffer layers at the electrode interfaces in OPVs . Later, it was shown that proper design of SSM molecules can control the molecular orientation, structural order, and functionalities at the surface of the films . Furthermore, the electronic structures of the PHJ at the interface can be tuned through the molecular dipoles or the energy structures of the monolayers .…”
Section: Preparation and Characterization Of Planar Heterojunctionsmentioning
confidence: 99%
“…In addition to the intrinsic dipoles from the symmetric molecules at the surface, the aligned permanent dipoles of asymmetric molecules on the surface can induce a large shift in the vacuum levels. This has been achieved by using SSMs of fluoroalkylated molecules, such as F‐PCBM and P3DDFT (see Figure ), because the fluoroalkyl chains have strong permanent dipole moments. Depending on the density of the fluoroalkyl chains, the shift of the vacuum level at the film surface can be controlled.…”
Section: Preparation and Characterization Of Planar Heterojunctionsmentioning
confidence: 99%
“…Another surface segregated monolayer with different orientation was also examined with SOWG. We previously reported that polythiophene with alternating substitution of semifluoroalkyl and alkyl chains (P3DDFT, Scheme ) also forms a surface segregated monolayer in mixed films . However, in contrast to P3BT‐F 17 , the orientation of P3DDFT on the surface is edge‐on and parallel to the interface because the semifluoroalkyl chains are attached to the side chains.…”
mentioning
confidence: 99%
“…In that study, the PCBM was spin-coated from dichloromethane, a marginal solvent for P3HT, onto the P3HT underlayer. Through several follow-up investigations over the past few years, it has been further revealed that PCBM can diffuse into amorphous regions of P3HT during spin-coating, even when dichloromethane is utilized as a solvent for PCBM. Chen et al reported that the diffusion of PCBM in P3HT was attributed to the swelling of P3HT during the spin-coating with PCBM and that the PCE of the bilayer device could be improved by up to 2.41%, a value comparable to that of the BHJ control device (2.47%). Furthermore, Gevaerts et al demonstrated that the PCE of a thermally annealed P3HT/PCBM bilayer device (2.38%) outperformed that of the BHJ control device (1.23%).…”
Section: Introductionmentioning
confidence: 99%